Employer learning and the returns to schooling - Bauer, Thomas K. [Verfasser]; Haisken-DeNew, John P. [Verfasser] (My University, 2000)
"We examine the dynamic role of education and experience as determinants of wages. It is hypothesized that an employee’s education is an important signal to the employer initially. Over time, the returns to schooling should decrease with labor market experience and increase with initially unobserved ability, since the employer gradually obtains better information on the productivity of an employee. Replicating US studies using data from a large German panel data set (GSOEP), we find no evidence for the employer learning hypothesis for Germany. Differentiating blue-collar and white-collar workers and estimating quantile regressions, however, leads to the conclusion that employer learning takes place for blue-collar workers at the lower end of the wage distribution. We further show, that information on the productivity of an employee is to a large extend private." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; T 3.5 Statistik; Bildungsertrag; Einflussfaktor; Empirische Untersuchung; Sozioökonomisches Panel